If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5p + -3) = 5(p + -2) Reorder the terms: 3(-3 + 5p) = 5(p + -2) (-3 * 3 + 5p * 3) = 5(p + -2) (-9 + 15p) = 5(p + -2) Reorder the terms: -9 + 15p = 5(-2 + p) -9 + 15p = (-2 * 5 + p * 5) -9 + 15p = (-10 + 5p) Solving -9 + 15p = -10 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -9 + 15p + -5p = -10 + 5p + -5p Combine like terms: 15p + -5p = 10p -9 + 10p = -10 + 5p + -5p Combine like terms: 5p + -5p = 0 -9 + 10p = -10 + 0 -9 + 10p = -10 Add '9' to each side of the equation. -9 + 9 + 10p = -10 + 9 Combine like terms: -9 + 9 = 0 0 + 10p = -10 + 9 10p = -10 + 9 Combine like terms: -10 + 9 = -1 10p = -1 Divide each side by '10'. p = -0.1 Simplifying p = -0.1
| -5+8y-4y=0 | | 6=n-(-14) | | f(n)=8+3(n-1) | | -11=25x+13-x | | 0.5k+0.17=0.42 | | 8x^5-192x^4+1536x^2=0 | | 19x-45-9x=5 | | x^2-5mx+6m^2+m-1=0 | | x^3-24x^2+192=0 | | 53=17x-10-8x-9 | | 8+x+9=8+x+9 | | Y+2(-1)=0 | | 10r-84=4 | | 6X+15-5(X+7)+30=12 | | 6x-5=6(x-1)+14 | | 10-43=2x+21 | | (9x+18)=54 | | 6y+5x=28 | | x^7=2.5 | | 3x-6=-2x+11 | | x^5-2x^4-x-3=0 | | 2c+4x=23 | | Y-3(-1)=4 | | Y-3(-2)=4 | | 3.0+3.0x=3.2 | | 4-x=[2-3x] | | 7-.625x=-2 | | .75x=180 | | 4(0)+2y=6 | | 100=10(logI-logI[0]) | | ax+by+1=0 | | 4(-1)+2y=6 |